Effect of supplementation of concentrate on reproductive performance of grazing Ganjam goat in its native tract - RAY, B; DEHURI, P K; MISHRA, S K; SWAIN, R K; MOHANTY, D N; DASH, S K (The Indian Journal of Animal Sciences, 2012)
To study the availability of nutrients to grazing Ganjam goats, survey was carried out in the native tract and 17 shrubs were indentified. Further, 1 digestibility trial was conducted by using indicator method. To assess the effect of supplementary feeding, total 100 pregnant Ganjam does at mid pregnancy were chosen and randomly allotted to 4 treatments i.e. T1 (control) and 3 concentrate supplementation groups, viz. T2 (50g), T3 (100g) and T4 (150g) and supplemental feeding was made for minimum 2 months pre-partum to maximum 60days of lactation. The body weights of does were recorded at the beginning of experiment and subsequently at fortnightly intervals of prepartum and postpartum. The proximate composition of the shrubs revealed that the average DM, CP, CF, EE, TA and NFE were 37.72, 13.52, 23.35, 5.12, 8.92 and 49.10%, respectively, on DM basis. The digestibility coefficient of DM, OM, CP, EE, CF and NFE were 46.85, 46.83, 51.77, 43.33, 42.00 and 46.18% on dry matter basis, respectively. The average body weight gains during prepartum were 2.680Â±0.018, 3.056Â±0.027, 3.436 0.027, and 3.712 0.024 kg, respectively in T1,T2, T3 and T4, respectively. There was no significant difference in the body weight of does between groups at 0th, 15th, 45th day of post partum. At 60th day of post partum, the body weight of T3 and T4, was significantly higher than that of T1. The body weight loss of the does in groups T1, T2, T3 and T4 during post partum 60 days feeding period have been recorded as 2.744, 1.596, 0.768 and 0. 320 kg for T1, T2, T3 and T4, respectively.